PENGARUH PENUNDAAN PENANGANAN DAN PEMBERIAN PAKAN SESAAT SETELAH MENETAS TERHADAP PERFORMANS AYAM RAS PEDAGING - Sudding, Hardianti, Andi Faisal (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. This study aims to determine the effect of treatment delays and feeding after hatching on growth rate and feed efficiency of broiler. This study was conducted from March to April 2012, in the Poultry Production Science Laboratory, Department of Animal Production, Faculty of Animal Husbandry, University of Hasanuddin, Makassar. This study is based on completely randomized design (CRD) with 3 treatments and 4 replications. The treatments were applied, namely U1: Delays handling and feeding 12 hours after hatching, U2: Delays handling and feeding 42 hours after hatching, U3: delay handling and feeding 72 hours after hatching. Parameters measured were early treatment weight, feed consumption, water consumption, weight gain, final body weight and feed conversion. Results of analysis of variance showed that the delay handling and feeding 12 hours, 42 hours, and 72 hours after hatching significant (P <0.05) on body weight beginning of treatment, significant (P <0.05) on feed consumption, not influence (P> 0.05) on the consumption of drinking water, a significant effect (P <0.05) weight gain, significant (P <0.05) on final body weight had no impact (P> 0.05 ) to broiler feed conversion. The conclusion of this study that the chickens get the handling and feeding early will consume more feed that impact on better growth. However, delay in the handling and feeding had no impact on water consumption and feed conversion.